PENGARUH PEMBERIAN JUS KACANG HIJAU DAN MADU TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL - Sri Wulan; Muniar Vindralia (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Anemia is a problem that often accompanies pregnancy. The most common anemia during pregnancy is nutritional anemia caused by iron deficiency. Pregnant women are considered to have anemia if their hemoglobin (Hb) level <11 gr / dL. Anemia can worsen the birth process. Anemia can be overcome with pharmacological and non-pharmacological treatments, one of the non-pharmacological treatments for the prevention of anemia in pregnant women is to consume green bean juice and honey. Because green beans and honey contain iron and vitamins that can increase hemoglobin levels. This study aims to determine the effect of giving green bean juice and honey on hemoglobin levels in pregnant women. The research method used was quasi-experimental (Quasi Experiment) with one group pre and post test design. The study population was all pregnant women who performed ANC at the Maiharti West Range Midwife clinic. The sampling technique used purposive sampling with the results of 19 pregnant women. The results showed that from using the Paired Sample T-Test analysis of giving green bean juice and honey to increase hemoglobin levels in pregnant women where the p 0,00 <Î± = 0,05. It can be concluded that the administration of green bean juice and honey is effective in increasing hemoglobin levels